Lower extremity cooling reduces ischemia-reperfusion injury following Zone 3 REBOA in a porcine hemorrhage model. Issue 3 (September 2018) - Simon, Meryl A.; Tibbits, Emily M.; Hoareau, Guillaume L.; Davidson, Anders J.; DeSoucy, Erik S.; Faulconer, E. Robert; Grayson, J. Kevin; Neff, Lucas P.; Johnson, M. Austin; Williams, Timothy K.
Abstract : BACKGROUND: New strategies to mitigate ischemia during REBOA and to prolong its maximal duration are needed. We hypothesized that simple external cooling of the hind limbs would decrease ischemia-reperfusion injury following prolonged Zone 3 REBOA. METHODS: Twelve swine were anesthetized, instrumented, splenectomized, and then underwent 15% total blood volume hemorrhage. Animals were randomized to hypothermia or control followed by 4 hours of Zone 3 REBOA, resuscitation with shed blood, and 3 hours of critical care. Physiologic parameters were continuously recorded, and laboratory specimens were obtained at regular intervals. Baseline and end-of-study muscle biopsies were obtained for histologic analysis. RESULTS: There were no significant differences between groups at baseline or after hemorrhage. Maximum creatine kinase was significantly lower in the hypothermia group compared with the normothermia group (median [interquartile range] = 3, 445 U/mL [3, 380–4, 402 U/mL] vs. 22, 544 U/mL [17, 030–24, 981 U/mL]; p < 0.01). Maximum serum myoglobin was also significantly lower in the hypothermia group (1, 792 ng/mL [1, 250–3, 668 ng/mL] vs. 21, 186 ng/mL [14, 181–24, 779 ng/mL]; p < 0.01). Fascial compartment pressures were significantly lower during critical care in the hypothermia group ( p = 0.03). No histologic differences were observed in hind limb skeletal muscle. CONCLUSIONS: External cooling during prolonged Zone 3 REBOA decreased ischemic muscle injury and resulted in lower compartment pressures following reperfusion. Hypothermia may be a viable option to extend the tolerable duration of Zone 3 occlusion, beyond what is currently achievable. Future survival studies are required to assess functional outcomes.